The nature of conflict in design agency-supplier-business customer triads in NPD projects - FU, JIE (2019)
The dissertation aims to examine the inter-organizational relationship and conflict in design agency- supplier-business customer triads during new product development, especially how to manage the inter-organizational conflict among three parties. The previous studies have primarily focused on the dyadic client-supplier relationship and client-design agency relationship. With the emerging of the networking concept, it reveals the necessity of studying the triadic relationship among design agency-supplier-business customer. This study has applied qualitative research and the data was collected from a semi-structured interview based on six case studies. The data was mainly from a design agency perspective. An account manager and a designer were invited to provide insight for each case. Also, the previous studies have paid attention to the relationship between the intensity of inter-organizational conflicts and NPD performance as well as the relationship between conflict-handling style and NPD performance in a dyadic client-supplier collaboration. Therefore, this research places the context in a specific design agency, supplier and business customer triad with the purpose of investigating the inter-organizational relationship in different industries and different types of projects.